From permafrost soil to thermokarst lake sediment: A view from C:N:P stoichiometry - Ren, Ze; Li, Xia; Zhang, Cheng; Wang, Qing; Fang, Le; Cao, Shengkui; Yu, Jinlei (Frontiers in Environmental Science, 2022)
Thermokarst lakes are formed as a result of thawing ice-rich permafrost, transforming vast permafrost soil into lake sediment and changing the biogeochemistry of carbon (C), nitrogen (N), and phosphorus (P). Degraded permafrost soil and thermokarst lake sediment are two distinct fates of pristine permafrost in the thermokarst processes. However, we do not clearly understand the differences and relationships between degraded permafrost soil and thermokarst lake sediment from a stoichiometric perspective. In this study, 44 thermokarst lakes across the Qinghai-Tibet Plateau were investigated to collect lake sediment and surrounding degraded permafrost soil. In general, C, N, and P concentrations as well as C:N, C:P, and N:P ratios in soil and sediment decreased with increasing latitude, while increased with increasing mean annual precipitation. The degraded permafrost soil had much higher C, N, and P concentrations and C:N:P stoichiometric ratios than the lake sediment, particularly for C. Moreover, the concentrations of C, N, and P, as well as the ratios of C:P and N:P in sediment showed significant positive relationships with their corresponding components in soil but with different slopes. Standard major axis regression showed allometric scaling relationships between C, N, and P. The C:N:P ratio was 269:18:1 in degraded permafrost soil and 178:15:1 in lake sediment. The results suggest that the process from pristine permafrost to lake sediment releases more C, N, and P than the process from pristine permafrost to degraded permafrost soil, and that C changes more profoundly than N and P. Moreover, thermokarst processes substantially change the elemental balance and decouple the C:N:P relationship between degraded permafrost soil and lake sediment, suggesting that the further transformation from degraded permafrost soil to lake sediment will lose more C, which can be intensified by increasing precipitation. The results enriched our understanding of the variations in C, N, and P biogeochemistry during thermokarst processes.